PERAN PEMERINTAH DAERAH DALAM MASALAH PERDATA TERKAIT SEWA-MENYEWA PRIBADI DITINJAU DARI PERATURAN PERUNDANG-UNDANGAN (PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 51 TAHUN 1960 DAN KITAB UNDANG-UNDANG HUKUM PERDATA) - Muhammad Ruen Wijokangko Wijokangko; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2022)
That in the case of land use without the rightful permit or his proxies in accordance withGovernment Regulation in Lieu of Law Number 51 of 1960. So for people who feel their land isoccupied by other people without the rightful permit, they can apply for legal protection to thegovernment in order to complete the use of land without the right of permission or their proxies,this is in accordance with the authority granted by the law that local governments can control orvacate the use of land without the right of permission or their proxies in order to bring order totheir territory. Even if in this case there is a civil problem, the government can enter into thesettlement of this problem with a note that the lease agreement between the parties has ended or isnull and void or there is a legal defect in it and the af airs between the parties have automaticallyended. So, with the lease ending in accordance with the Civil Code, the person occupying the landwithout the right to use the land is included in the category of use without the rightful permissionor his proxies. And this is where the government can play a role in providing legal protection tothe community in the context of structuring its territory, not to declare someone's ownership.